If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(F+5)=6F+2
We move all terms to the left:
(F+5)-(6F+2)=0
We get rid of parentheses
F-6F+5-2=0
We add all the numbers together, and all the variables
-5F+3=0
We move all terms containing F to the left, all other terms to the right
-5F=-3
F=-3/-5
F=3/5
| -1901+y/35=y-1969 | | 24=-n/3 | | -36=3p-6=-15 | | 6r=1+6r=11 | | x(x+5)^2=0 | | 4-3x=32 | | 2x-3=5/6x+3 | | 9(x-4)=-3(x-9) | | 7m-(3-m)=12 | | 5x-21=x+3 | | -.5x-3.69=x-1.9-2.39 | | 11•3•x=x | | 8=3/5(7x+25) | | 46=2(10+n) | | 3/8k-1/7=1/4 | | 3(x+6)=3x+16 | | 8x^2+12=102 | | 0=9x^2-5 | | 11*3*x=x | | 1/2x+4=-3+1/2x+7 | | 2x+4=-(-7×+6) | | 9|x+8|+10=55 | | 7x-10x+18-2x=-5 | | 12x^2-48x-36=0 | | -9m-4=-139 | | 230+w=1265 | | .87y+3=y-0.9 | | 4h-2=h+3*2 | | 8+8(x-4)=8-4(x-7) | | -2|x+3|=-20 | | 12*4m=16 | | x^2+13x+52=10 |